(3GdCNHGQ HhaGI GdeNJGQ (B( (3Udi Gddg Ydjg hSde (B)s - (3eMeO Hf YHO Gddg Hf eMeO GdbjSj GdOeTbqj GdTGaYqj, TeS GdOjf, GdTgjQ HGHf fGUQ GdOjf,J (B842 (3g` s ((3OeTb s)
(3ChdgG (B:s
(3GdMeO ddg Gdedc GdOjGf , GdYXje GdSdWGf hHYO Ef dG Edg EdG Gddg hMOg dG TQjc dg GdgG Ndb GdNdb HGdbOQI s
(3BNQgG (B:s
(3Ydjc ef Gddg GdSdGe eMHI hGONdJ LfGJ ef GdYOf QGVjkG BNQ GdENHGQ HhaGI GdeNJGQ s
(3HgG fXGe GdJYbjHIs
(3cJHJ HNW bdjd GdfbWs
(3Ydi MGTjI fSNJfG SeGY HNW GdeDda hHBNQgG SeGY SfI (B836 (3Ydi GdeDda ef YOI YdeGA efge GdfGSN faSg hTgO GdeDda Ydi gPG GdSeGY hELGRI HNWg hUaMg GdZdGa CjVkG HNW GdeDda s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs